Nursing in Saudi Arabia: Reflections on the experiences of South African nurses - Dalena van Rooyen; Colette D. Telford-Smith; Johanita Strümpher (AOSIS, 2010)
The purpose of the study was to describe and reflect on the lived experiences of the South African nurses residing and working in the Kingdom of Saudi Arabia. A qualitative, exploratory, descriptive and contextual design with a phenomenological approach was adopted. Data were collected by means of individual interviews and the personal journals of the nurses who met the sampling criteria. The data analysis was done according to Tesch's descriptive method (in Creswell 1994). The main theme that emerged was one of 'cultural diversity'. Sub-themes related to the nurses' religious/spiritual, environmental, emotional/psychological and professional experiences were also identified. A literature control was undertaken to verify the results. Limitations were highlighted, conclusions were drawn and recommendations relating to nursing research, education and practice were made. Opsomming Die doel van die studie was om die lewenservarings van Suid-Afrikaanse verpleegkundiges wat in die Koningkryk van Saoedi-Arabië werksaam en woonagtig is, te beskryf en daaroor te besin. 'n Kwalitatiewe, verkennende, beskrywende en kontekstuele navorsingsontwerp of strategie van ondersoek, vanuit 'n fenomenologiese benadering, is vir die doel ingespan. Data is ingesamel aan die hand van individuele onderhoude met deelnemers wat aan die kriteria vir insluiting by die steekproef voldoen het en persoonlike joernale wat deur hierdie deelnemers bygehou is. Data- ontleding is volgens die beskrywende metode van Tesch (in Creswell 1994) gedoen. Die hooftema voortspruitend uit die navorsing was dié van 'kulturele diversiteit'. Verdere temas ten opsigte van verpleegkundiges se godsdienstige/geestelike, omgewings-, emosionele/psigiese en professionele ervarings is ook geïdentifseer. 'n Literatuurkontrole is onderneem om die navorsingsbevindinge te verifieer. Beperkings is uitgelig, en gevolgtrekkings en aanbevelings gerig op verpleegkundige navorsing, onderrig en praktyk is gemaak.